Modified Data Encryption Standard Algorithm for Textbased Applications - Mohamed Khmag, Asem Ib. (2006)
Today security is the important thing that we need to transfer data from location to another safely. As there is strong security, there is great hacker and spies at the other side. Therefore, many models and systems are looking for an ideal method to provide a secure environment for better optimization of the electronic connected-world. Cryptography accepts the challenge and plays the main role of the modern secure communication world. The purpose of this thesis is to introduce and demonstrate a new algorithm for Internet and e-mail security. The proposed algorithm was developed based on the combination of symmetric and asymmetric algorithm whereas the length of the key and digital signature was considered. In this manner, the length of the key would not affect the time execution of this algorithm and digital signature in the end of message would increase the authentication between the sender and the recipient.The main steps in this algorithm started with reading the plain text "original message" from the user. The second step is to apply the hash method on this message by using shuffle mechanism. Now the message is ready to do the encryption process that is dividing the text message to 128 8-bit for each four sub keys, so if the text message less than 128 8-bit then use another sub key. The last step is to send the message to another side (the recipient). To retrieve the original message the recipient must apply the inverse of all the previous stages i.e. rehashing and decryption. In this study comparison between the proposed algorithm and RSA algorithm (asymmetric algorithm) was examined and successful results were obtained. Because of its short time execution and higher authentication, using this algorithm will ensure the security for internet applications.